Some Properties of Superplasticized and Retarding Concrete Under Effect of Accelerated Curing Methods (Journal of Engineering, 2012)
In recent decades, tremendous success has been achieved in the advancement of chemical admixtures for Portland cement concrete. Most efforts have concentrated on improving the properties of concrete and studying the factors that influence on these properties. Since the compressive strength is considered a valuable property and is invariably a vital element of the structural design, especially high early strength development which can be provide more benefits in concrete production, such as reducing construction time and labor and saving the formwork and energy. As a matter of fact, it is influenced as a most properties of concrete by several factors including water-cement ratio, cement type and curing methods employed.Because of accelerated curing is deemed one of methods that achieved high early age strength of concrete and has been grown only gradually. So, the prime aim of this research work is to provide information about the some desired properties of superplasticized and retarding concrete succumbed to accelerated curing methods, such as compressive strength and water absorption and compared it with their corresponding normally curing concrete. Besides, the research discusses the influence of surface texture of aggregate and over-dosing for admixture on performance concrete in such as that conditions. The test results revealed that effect of admixture on properties of concrete are dependent upon it dosage, surface texture for aggregate andtemperature used for curing